Oral Presentations Abstracts: DECISION-MAKING ETHICS WITH REGARD TO LIFE-SUSTAINING INTERVENTIONS: SUMMONING WHAT OTHER PATIENTS CHOSE - STERIE, Anca; RUBLI TRUCHARD, Eve; JOX, Ralf J (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Health decisions occur in a rich context in which social influences are omnipresent. The tendency to compare oneself with others has been described as one of the critical social factors influencing decision making. Based on a collection of 43 audio-recordings of hospital admission encounters which were analyzed though a conversation analytic methodology, we present findings and reflections in regard to how patients and physicians discuss cardio-pulmonary resuscitation. The phenomena of interest concerns how and when patients and physicians refer to what other people decide (for example: “Often the patients tell us: No futile care”). This practice is encountered in 6 of the conversations recorded. Reference to other people’s decisions is a way to talk about options, but it does much more than just enumerating them. As a resource in interaction, this reference is employed when the patient can’t or doesn’t express a preference (thereby clarifying options) or when the preference the patient expressed is problematic (because contrary to expectations). By using this reference, decision making is projected as a matter of membership to a group of individuals, and not as a matter of individual prognostic.The ethical implications of referring to other people’s choices are significant, since it can influence the patient and pose a serious threat to autonomous decisions. We argue that findings such as ours, stemming from data-driven studies of healthcare communication, are pivotal for informing ethics education in its effort to address the biases that physicians impose upon patients during decision making.